Rural women's empowerment and rural development in Nigeria's South-South Geopolitical Zone - URHIBO , Bridget Onajite; ORHERO , Abraham Ejogba (Universitas PGRI Madiun, 2023)
In the south-south geopolitical zone of Nigeria, the study examined the relationship and effects between rural women's empowerment and rural development. Data were gathered through a survey of 750 people using a non-probability sampling technique and a cross-sectional research design. Of the 750 questionnaires that were distributed, 476 were collected and examined. Data gathered through the use of percentages, Pearson product moment correlation, and linear regression analysis was examined using SPSS version 23. The study showed a strong connection between rural development and women's empowerment in Nigeria's south-south geopolitical region. The study concludes that rural women's empowerment influences rural development in Nigeria's south-south geopolitical zone in a favorable and statistically significant manner. Based on these findings, the study makes several recommendations; including that government empowerment policy should always consider the female gender for necessary upliftment as this will help to improve their status and rural development in Nigeria.